1988
DOI: 10.1254/jjp.48.395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synthetic ω-Conotoxin on the Contractile Responses of Segments of Rat Ileum, Stomach Fundus and Uterus and Guinea Pig Taenia Coli

Abstract: Abstract-The effect of synthetic w-conotoxin (w-CgTX) on the contractile re sponses of segments of rat ileum, stomach fundus and uterus and guinea pig taenia coli were investigated. w-CgTX (10-9-5 X 10-6 M) did not inhibit the contractile responses of al! smooth muscle segments to high KCI and/or ACh. However, unexpectedly, w-CgTX (3x10-7-10-5 M) alone caused dose-dependent con traction of segments of the stomach fundus and uterus. These contractile responses to w-CgTX alone depended upon the presence and/or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
7
2
Order By: Relevance
“…It has been found that high concentrations of conotoxin (O.3-1O0M) produced contractions of rat gastric fundus and uterus, and enhanced responses of the uterus to acetylcholine and KCI (Ichida et al, 1988). We did not observe any such effects with the lower concentrations of conotoxin used in any of the tissues we studied.…”
Section: Effects Ofconotoxin On Nanc Transmissioncontrasting
confidence: 63%
“…It has been found that high concentrations of conotoxin (O.3-1O0M) produced contractions of rat gastric fundus and uterus, and enhanced responses of the uterus to acetylcholine and KCI (Ichida et al, 1988). We did not observe any such effects with the lower concentrations of conotoxin used in any of the tissues we studied.…”
Section: Effects Ofconotoxin On Nanc Transmissioncontrasting
confidence: 63%
“…From the previous experiments performed in our lab, we have experienced that at least rat stomach fundus tends to be more responsive to spasmogenics than to spasmolytics, particularly when a combination of these stimulant and relaxant constituents coexists (41). There have also been reports in the literature on the specific spasmogenic activity of particular compounds in rat stomach fundus that had a spasmolytic effect in other tissues from rat and other species (42,43). On the other hand, rat stomach fundus has been reported to be less responsive to spasmolytic activity (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…These con tractile responses to omega-CgTX depended upon the presence and/or the influx of ex tracellular calcium and these responses were inhibited by calcium antagonists, suggesting that omega-CgTX might have a calcium agonist-like effect on smooth muscles (6). However, omega-CgTX caused only a nega tive inotropic response in the isolated, blood perfused dog atrium.…”
mentioning
confidence: 93%
“…It was reported that omega-CgTX caused dose-dependent contraction in segments of the rat stomach fundus and uterus (6). These con tractile responses to omega-CgTX depended upon the presence and/or the influx of ex tracellular calcium and these responses were inhibited by calcium antagonists, suggesting that omega-CgTX might have a calcium agonist-like effect on smooth muscles (6).…”
mentioning
confidence: 97%
See 1 more Smart Citation